Custom-made healthcare: An experimental investigation - Claudia Keser; Claude Montmarquette; Martin Schmidt; Cornelius Schnitzler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
In this paper, we investigate in a controlled laboratory experiment physician behavior in the case of payment heterogeneity. In the experiment, each physician provides medical care to patients whose treatments are paid for either under fee-for-service (FFS) or capitation (CAP). We observe that physicians customize care in response to the payment system. A FFS patient receives considerably more medical care than the corresponding CAP patient with the same illness and treatment preference. Physicians over-serve FFS patients and under-serve CAP patients. After a CAP payment reduction in the experiment we observe neither a quantity reduction under CAP nor a spillover into the treatment of FFS patients.
Keywords: C91; I12; I18; 330; experimental economics; physician reimbursement; capitation; Fee-For-Service; customization; fee regulation